2019
DOI: 10.1371/journal.pone.0221292
|View full text |Cite
|
Sign up to set email alerts
|

Political priority and pathways to scale-up of childhood cancer care in five nations

Abstract: Background Despite increasing global attention to non-communicable diseases (NCDs) and their incorporation into universal health coverage (UHC), the factors that determine whether and how NCDs are prioritized in national health agendas and integrated into health systems remain poorly understood. Childhood cancer is a leading non-communicable cause of death in children aged 0–14 years worldwide. We investigated the political, social, and economic factors that influence health system priority-settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The methodology is presented in detail elsewhere and summarised in appendix panel 4 (pp. 21-22) 71,72 In each of the five countries studied, philanthropic organizations, foundations or private institutions had been the first to establish services for childhood cancer, often working with international partners (panel 4). Childhood cancer had not been a priority in the publicly funded health systems of these countries due to political instability and competing policy priorities.…”
Section: Priority Setting For Childhood Cancers: Case Studies From Fimentioning
confidence: 99%
“…The methodology is presented in detail elsewhere and summarised in appendix panel 4 (pp. 21-22) 71,72 In each of the five countries studied, philanthropic organizations, foundations or private institutions had been the first to establish services for childhood cancer, often working with international partners (panel 4). Childhood cancer had not been a priority in the publicly funded health systems of these countries due to political instability and competing policy priorities.…”
Section: Priority Setting For Childhood Cancers: Case Studies From Fimentioning
confidence: 99%
“…A recent systematic review demonstrated that although the few studies conducted to date uniformly concluded that childhood cancer treatment in LMICs is cost‐effective, many did not comprehensively capture all the associated costs of treatment 6 . In addition, to our knowledge, very few rigorous studies were conducted in sub‐Saharan Africa, which will account for nearly one‐half of the total global childhood cancer burden by 2030 and where health systems routinely face acute resource constraints, resulting in difficult decisions concerning how best to allocate scarce public funds 1,7,8 . Previous work by our team demonstrated that operating a childhood cancer treatment center in Accra, Ghana, is very cost‐effective by international standards 9 .…”
Section: Introductionmentioning
confidence: 99%
“…These efforts, including partnerships with paediatric cancer centres in HICs, promote capacity building, education of healthcare personnel, implementation of treatment strategies, and establishment of research programmes adapted to local capacity and needs 11. However, recognition of the limits of such initiatives in terms of health system integration and sustainability has prompted increasing emphasis on the importance of national childhood cancer strategies, and evidence to support governmental priority-setting accordingly 14…”
Section: Introductionmentioning
confidence: 99%